Tool for Assessing Cultural Competence Training (TACCT) (Out of Print) - Desiree Lie (Association of American Medical Colleges, 2006)
Abstract This is a resource for measuring teaching and learning of cultural competence in the undergraduate medical school curriculum. Given increasing diversity in the U.S. population and continued evidence of health and health care disparities, it is critically important that health care professionals are educated on how their own and their patients' demographic (e.g., gender, income, race and ethnicity, etc.) and cultural (e.g., language, religion, etc.) factors influence health, health care delivery, and health behaviors. In 2000, the Liaison Committee on Medical Education introduced two standards about cultural competence that inspired medical schools to integrate cultural competence education into the undergraduate curriculum. The Tool for Assessing Cultural Competence Training (TACCT) was developed to advance these efforts. TACCT is a 67-item self-administered assessment tool that can be used by medical schools to examine all components of the entire medical school curriculum. TACCT enables schools to identify gaps and redundancies in their curricula; gather information from various stakeholders such as students and faculty; and serves as a blueprint of where, what, and when cultural competence content exists in the curriculum. This enables schools to make the best use of opportunities and resources to integrate cultural competence content. The TACCT can be used for both traditional and problem-based curricula.